Food in the Sea: Size Also Matters for Pelagic Fish - Queiros, Quentin; Fromentin, Jean-Marc; Gasset, Eric; Dutto, Gilbert; Huiban, Camille; Metral, Luisa; Leclerc, Lina; Schull, Quentin; McKenzie, David J.; Saraux, Claire (Frontiers in Marine Science, 2019)
Small pelagic fish are key components of marine ecosystems and fisheries worldwide. Despite the absence of recruitment failure and overfishing, pelagic fisheries have been in crisis for a decade in the Western Mediterranean Sea because of a marked decline in sardine size and condition. This situation most probably results from bottom-up control and changes in the plankton community towards smaller plankton. To understand such an unusual phenomenon, we developed an original and innovative experimental approach investigating the mechanisms induced by a reduction in the quantity and size of sardine prey. While experimentations offer the unique opportunity to integrate behavior and ecophysiology in understanding key demographic processes, they remain rarely used in fisheries science, even more so on small pelagics due to the notorious difficulty to handle them. The results revealed that food size (without any modification of its energy content) is as important as food quantity for body condition, growth and reserve lipids: sardines that fed on small particles had to consume twice as much as those feeding on large particles to achieve the same condition and growth. Such a strong impact of food size was unexpected and may reflect a different energy cost or gain of two feeding behaviors, filter-feeding versus particulate-feeding, which would have to be tested in further study. As increasing temperature favors planktonic chains of smaller size, climate change might actually accelerate and amplify such phenomenon and thus strongly affect fisheries.